Perkembangan e-commerce di era digital : peluang dan tantangan - widiyastutik, meilisa (Maliki Interdisciplinary Journal, 2026)
In this digital age, online buying and selling, or e-commerce, has changed the way people trade, both globally and in Indonesia. This article reviews how e-commerce has developed in terms of technology, business, and its impact on society. Special attention is given to the growth potential of the online market for Micro, Small, and Medium Enterprises (MSMEs), innovations in digital payment systems, and existing challenges such as legal regulations, data privacy protection, and competition from large platforms. Based on literature studies and experience in assisting MSMEs at UIN Maulana Malik Ibrahim Malang, this article highlights the importance of digital marketing strategies, digital transformation in halal businesses, and efforts to improve sales capabilities through digital marketing carried out by experts and practitioners in Malang. The recommendations in the final section include policy measures, improving digital literacy, and collaboration between universities and the business world to create a friendly and secure e-commerce environment for MSME players